(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Millions of individuals throughout the globe earn a career by collecting, sorting, recycling, and selling goods that someone else has discarded. Rag picking is referred to in a variety of ways. It is more generally referred to as a rag picker. Most rag pickers are impoverished, uneducated and from rural immigrant households, which is a commonality around the globe. It is common for migrants to come to the city in search of a better life by picking up trash. Rag pickers in Maharashtra’s capital city are living in appalling circumstances, according to recent research. Disgusting living conditions are the norm here. There is a pressing need to ensure that rag pickers have adequate working conditions and basic amenities so that their contribution to social progress may be properly recognised. In order to make a meaningful shift in income and wealth disparity, one must look at the long term. Either an increase or reduction in inequality may be caused by changes in the employment structure of an economy.